SISTEM INFORMASI PENGGAJIAN PADA CV AL-FATTAH PLAFON INDRAMAYU BERBASIS DESKTOP - Diana, Esti; Upayarto, Budi (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2025)
This study aims to analyze, design, implement, and test an payroll information system at CV Al-Fattah Plafon Indramayu based on a desktop platform. In this study, the author obtained data by conducting observation, interviews, and literature studies. The research method used is the PIECES analysis approach, and the system development method is the waterfall approach. The implementation of the payroll information system was designed using Visual Basic.Net 2010 programming language with a MySQL database, and the system was tested using blackbox testing. The system has controlled access that can be managed with user login facilities, displaying application menus according to user authority. In data processing, users only input data into the system, and the system processes the data until the creation of payroll slips and employee salary reports. The results of the system testing can serve as a solution to the problems in the employee presence recording and employee salary calculation process at CV Al-Fattah Plafon Indramayu.